ANALYSIS OF APPLICATION PERFORMANCE TESTING USING LOAD TESTING AND STRESS TESTING METHODS IN API SERVICE - Mokhamd Hendayun; Arief Ginanjar; Yoan Ihsan (JURNAL SISFOTEK GLOBAL, 2023)
Testing an application is an important thing to do in software development. However, there are some tests that are sometimes missed after application development has been completed, such as performance testing. Performance testing is a type of test to ensure software will work properly under the expected workload. When performance testing is important to ensure that the functional needs of the system are running well. To ensure that the business objectives of the system are satisfactory and according to user needs can be done using Black Box Method. After ensuring the final results meet the specifications of the system needs, performance testing can be carried out. In performance testing, a load and stress testing methods are used to test the system, so as to be able to validate system performance are correct and determine the operating capacity of the system, with load limit at the break threshold and above the break threshold. This test is carried out to help determine how software can act well when accessed by several users together with a lot of data. This study conduct analyze the behavior of the system in the server environment that currently running and then optimize the configuration of the service and server to achieve concurrent users with 500 users at a time with jmeter as a performance test tools.